Consulting report – Inefficient management of the outsourced QA planning and testing between Telefónica and Indra - Silva Puente Arnao, María Angélica; Vilchez Rodriguez, Karla Solansh (Pontificia Universidad Católica del Perú, 2020)
Telefónica is a telecom company that operates in 14 countries in South America and Europe, offering products and services such as wireless telephony, mobile phones, internet, cable TV, among others. Its main competitive advantages are the design and differentiation of its products, as well as the global brand recognition. One of the countries where this company operates is Peru, where Telefónica is leader in the sector and has contributed to the development of the country's telecommunications infrastructure. Telefónica del Perú has a Quality Assurance (QA) team to ensure that all Customer Relationship Management (CRM) activities function without errors after a product is launched, so as not to affect commercial operations. Part of the quality control process is outsourced by Indra, a provider of information technology consulting services who is responsible for planning and executing tests for Telefónica del Perú. Nevertheless, there is currently a problem that is reflected in hours of inoperability of the CRM system and working hours of this supplier. The problem identified is the inefficient management of the outsourced QA planning and testing between Telefónica and Indra. This problem has generated unnecessary costs for Telefónica del Perú of S/ 547 million in lost sales opportunities (from January 2019 to January 2020), and S/ 307 thousand in unused working hours of Indra (from January to June 2020). Therefore, five solutions have been proposed through a Cooperation Model to help Telefónica del Perú to improve its relationship with Indra, to meet its objectives, and to continuously improve in order to offer products and services with the highest quality standards, providing the best experience for customers. The expected results are to reduce 70% of the costs of lost sales opportunities and unnecessary payments made to Indra.

Telefónica es una compañía de Telecomunicaciones que opera en 14 países de Sudamérica y Europa, ofreciendo productos y servicios, tales como telefonía inalámbrica, móviles, internet, cable TV, entre otros. Sus principales ventajas competitivas son el diseño y la diferenciación de sus productos, así como el reconocimiento de la marca a nivel global. Uno de los países donde opera es Perú, donde Telefónica es líder en el sector y ha contribuido en el desarrollo de infraestructura de telecomunicaciones del país. Telefónica del Perú cuenta con un equipo de Quality Assurance (QA) para garantizar que todas las actividades de Customer Relationship Management (CRM) funcionen sin errores luego del lanzamiento de un producto, a fin de no afectar las operaciones comerciales. Parte del proceso de control de calidad es subcontratado por Indra, un proveedor que brinda servicios de consultoría de tecnologías de información y es responsable de las actividades de planificación y ejecución de pruebas para Telefónica del Perú. Sin embargo, actualmente existe un problema que se ve reflejado en horas de inoperatividad del sistema CRM y de trabajo de este proveedor. El problema identificado es la gestión ineficiente de la planificación y ejecución de pruebas de QA. Este problema ha generado costos innecesarios para Telefónica del Perú por S/ 547 millones en oportunidad de ventas perdidas (de enero de 2019 a enero de 2020) y S/ 307 mil en horas inutilizadas de trabajo de Indra (de enero a junio de 2020). Por ello, se han propuesto cinco soluciones a través de un Modelo de Cooperación que ayude a Telefónica del Perú a mejorar la relación con Indra, se cumplan los objetivos y mejoren continuamente para ofrecer productos y servicios con los más altos estándares de calidad, brindándole la mejor experiencia a los clientes. Los resultados esperados son reducir el 70% de los costos de oportunidades de venta perdidas y pagos innecesarios realizados a Indra.
Keywords: Telefónica del Perú; Consultores de empresas; https://purl.org/pe-repo/ocde/ford#5.02.04